Analisis Perambatan Fatik Baja Pegas JIS SUP9 Yang Diberi Perlakuan Panas Austempering - Purga, Ahmad Kurniawan; Badaruddin, Moh.; Sugiyanto (Universitas Muhammadiyah Metro, 2024)
JIS SUP9 steel is known for its mechanical properties that are able to withstand continuous loads. In this regard, further observation is needed in order to comprehensively determine the strength and fatigue characteristic of JIS SUP9 steel which will be used to predict its service life by conducting both tensile and fatigue test experiments, then subjecting the steel to Austempering heat treatment with a salt solution at 800 degrees Celsius for 120 minutes followed by cooling to room temperature. The results of the tensile test showed the maximum stress of the steel indicating a higher strength of the steel to 1087.16 MPa hence the specimen became brittle. The fatigue test results showed that the specimen perpendicular to the rolling direction had a cycle of 60,000N and a crack propagation of 20.8 mm, whereas the specimen with the same rolling direction produced a cycle of 37,500N but a crack length of 21.2 mm. The test results showed the high cycle fatigue properties of the specimen because microstructure observations using Optical Microscopy (OM) and Scanning Electron Microscopy (SEM) revealing Pearlite, Bainite, and Ferrite phases. This is the reason and answer why JIS SUP9 Steel can still be relied on as a spring material for vehicles that carry loads.